CHEAP AND QUALITY DIFFERENCES FOR SUNFLOWER FRUIT. - Sofiev Saidvoishxon Saidmurodxonovich; Yuldashev Akmaljon Mexmonovich (Scholar Express Journals, 2021)
Separation of sunflower from the basket consumed by our people, introduction of mechanized hand-made, cheap SSS 1991 K maral technology provides information about varieties of sunflower. This technology also serves to sort and clean the sunflower from dust. It quickly and efficiently separates all products from the sunflower plant, which does not allow the quality to change.
Keywords: Sunflower, pistachio, oil, basket, shopping, waste, technology, fruit, cheap